Technical, tactical and movement analysis of men`s professional tennis on hard courts - Martinez-Galleg, R.; Guzmán, J.; Crespo, M.; Ramón-Llin, J.; Vuckovic, G. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: There is very little information in tennis relating performance to both the movement of the players and the effectiveness of their shots. This study aimed to identify differences between winners and losers in the volume and intensity of their movements, as well as in the effectiveness of their shots. METHODS: Matches (N.=8) at the 2011 ATP 500 tournament in Valencia (Spain) were recorded and analyzed using SAGIT, a computerized vision-tracking system. Data were split into points for movement analysis, and into games for stroke analysis. RESULTS: Players winning points used more offensive strategies and spent more time in the offensive zone than point losers. They also forced point losers to cover more distance at a higher speed. Game winners hit more winning shots, made fewer unforced errors, and were more effective than game losers. CONCLUSIONS: These results suggest that winner players controlled the game by playing more offensively and forcing losers to play in defensive positions, move greater distances at a faster speed, and make more errors.